2017
DOI: 10.1017/jfm.2016.812
|View full text |Cite
|
Sign up to set email alerts
|

Vortex dynamics for flow over a circular cylinder in proximity to a wall

Abstract: The dynamics of vortical structures in flow over a circular cylinder in the vicinity of a flat plate is investigated using particle image velocimetry (PIV). The cylinder is placed above the flat plate with its axis parallel to the wall and normal to the flow direction. The Reynolds number $Re_{D}$ based on the cylinder diameter $D$ is 1072 and the gap $G$ between the cylinder and the flat plate is varied from gap-to-diameter ratio $G/D=0$ to $G/D=3.0$. The flow statistics and vortex dynamics are strongly depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
24
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 33 publications
9
24
2
Order By: Relevance
“…It should be noted that previous experiments in the literature on vortex shedding in the vicinity of a rigid wall have indicated that the critical shedding parameters remain unaffected for models that are installed beyond two characteristic length scales away from the wall. [37,38]…”
Section: Tunnel Correctionsmentioning
confidence: 99%
“…It should be noted that previous experiments in the literature on vortex shedding in the vicinity of a rigid wall have indicated that the critical shedding parameters remain unaffected for models that are installed beyond two characteristic length scales away from the wall. [37,38]…”
Section: Tunnel Correctionsmentioning
confidence: 99%
“…The finite-time Lyapunov exponents (FTLEs) method (Haller & Yuan 2000; Haller 2001; Shadden, Dabiri & Marsden 2006; Green, Rowley & Haller 2007; Shadden, Astorino & Gerbeau 2010) and virtual dye visualization (VDV) (He et al. 2017; Wang et al. 2017) can extract Lagrangian coherent structures (LCSs) from complex flows based on tracking fluid particle trajectories.…”
Section: Experimental Methodologymentioning
confidence: 99%
“…The VDV can clearly visualize the interactions between different flow patterns by emitting virtual dyes with different colours (He et al. 2017; Wang et al. 2017).…”
Section: Experimental Methodologymentioning
confidence: 99%
“…The shed vortex from the upper part of the cylinder advects nearly parallel to the wall while the shed vortex from the lower part of the cylinder advects away from the wall and eventually crosses over the trajectory of the upper shed vortex. The final relative vertical positions of both vortices are opposite to those in the infinite fluid case [8,10]. He et al [10] found that a secondary vortex also forms, as a consequence of the roll-up of the separated wall boundary layer.…”
Section: Introductionmentioning
confidence: 94%
“…The final relative vertical positions of both vortices are opposite to those in the infinite fluid case [8,10]. He et al [10] found that a secondary vortex also forms, as a consequence of the roll-up of the separated wall boundary layer. At G/D = 1.0, regular vortex shedding is observed.…”
Section: Introductionmentioning
confidence: 94%